Evaluation of mediators of oxidative stress and inflammation in patients with acute appendicitis. (17th August 2016) - de Oliveira Machado, Sandra Lorena; Bagatini, Margarete Dulce; da Costa, Pauline; Baldissarelli, Jucimara; Reichert, Karine Paula; de Oliveira, Lizielle Souza; Lemos, Jéssica Gonçalves; Duarte, Thiago; Chitolina Schetinger, Maria Rosa; Morsch, Vera Maria
Abstract: Context : This study aims to explore the potential of new inflammatory markers for improving the challenging diagnosis of acute appendicitis (AA). Methods : Levels of IL-1, IL-6, IL-8, IL-10, CRP, INF-γ, and TNF-α in serum were measured in 73 patients with AA. Oxidative stress and antioxidant enzymes were analyzed. Results : Serum levels of interleukins, TNF-α, and INF-γ were significantly elevated in patients with appendicitis ( p  < 0.0001), except for IL-10, which presented decreased levels. There were no significant differences in SOD ( p  = 0.29), CAT ( p  = 0.19), or TBARS levels ( p  = 0.18), whereas protein carbonyls presented significant increase ( p  < 0.0001). Conclusion : Evaluating these biomarkers could aid in diagnosing AA.